Microteatro. - Montoya Hinojos, Norma Lilia; Guzmán Pérez, Paulina Clarissa; del Real, Gibran; Sandoval, Gabi (Cuadernos Fronterizos, 2008)
Fragmentos de relatos diferentes que apoyan un mismo sentimiento, o demuestran hacerlo.